The dose-dependent effect of acute ozone exposure on lung function and the efficacy of a Boysenberry apple powder blend (BerriQi®) in reducing throat irritation and symptom recovery time in healthy adults - Lomiwes D; Barnes M; Nicholls G; Ngametua N; Sawyer G; Kanon AP; Vangala G; Shaw O (Elsevier B V, 2025)
Urbanization and industrialization have impacted air quality and health, with ozone exposure linked to reduced lung function and increased respiratory issues. This study characterised the dose-dependent effect of acute, controlled ambient ozone exposure in an environmental chamber on lung function, then investigated the effect of BerriQi® Boysenberry and apple powder (BerriQi) ozone-induced respiratory irritation symptoms. In an incremental dose study, healthy adults were exposed to 0.1, 0.2 or 0.3 ppm ozone for 2 h. Forced vital capacity (FVC) and forced expiratory volume in 1 s (FEV1) were measured at designated timepoints up to 48 h after ozone exposure. This was followed by a randomised, double-blind, placebo-controlled crossover trial, with healthy adults (n = 20) who consumed either BerriQi or a placebo daily for 5 days before being exposed to 0.2 ppm ozone for 2 h. Respiratory irritation symptoms, including throat irritation (TI), soreness of cough (SOC), shortness of breath (SOB), and pain on deep inspiration (PODI), were assessed at designated timepoints up to 48 h after ozone exposure. Our results showed that 0.2 ppm ozone was the maximum tolerated dose that elicited a temporal decline in lung function in healthy participants and that BerriQi supplementation significantly reduced TI (p = 0.04), and may expedite the resolution of SOC, SOB and PODI after acute ozone exposure. These findings suggest that BerriQi may alleviate the severity and duration of ozone-induced respiratory irritation and highlights the potential of BerriQi as a dietary intervention for mitigating the respiratory effects of air pollution.